Characterization of physical, mechanical and morphological properties of unstitched and silk fibre-stitched woven Kenaf reinforced epoxy composites - Kermasha, Yasir Khaleel Ibrahim (2020)
Over the past decade, natural fibers (NFs) have attracted great attention to replace synthetic fibers in fiber-reinforced polymer composites owing to their acceptable mechanical properties, light weight, low cost, and biodegradability. In transportation sections, NFs are used to fabricate various car components, such as door panels, car roofs, dashboard components, mats, and wheels. In sports goods, several types of equipment such as surfboards, windsurfing boards, tennis rackets, badminton rackets, and golf clubs are fabricated using NFs. In general, fiber composites have poor through-thickness mechanical properties due to the absence of a z-direction binder. This problem becomes more critical with the use of NFs due to their lower strength compared to synthetic fibers. Stitching is a through-thickness toughening method, which is used to introduce fibers in the z-direction and achieve better through-thickness mechanical properties. The present study aimed to determine the mechanical properties of unstitched and silk fibrestitched woven Kenaf-reinforced epoxy composites. The woven Kenaf mat was stitched with silk fibre using a commercial sewing machine. The stitching length (SL) and stitching row (SR) spacing were five millimeters. The fivemillimeter stitching parameters were selected to make the stitching process easier by a commercial sewing machine and to minimize the damage to the stitched fiber. The specimens were fabricated using a hand lay-up method. In total, three specimens were fabricated (one unstitched and two silkstitched) with different stitching orientations. Following that, the specimens were cut in accordance with the standards of the American Society for Testing and Materials (ASTM), including ASTM D3039, ASTM D790, and ASTM D256 for tensile test, flexural test, and the Izod impact test, respectively. The tensile and flexural tests were conducted using an Instron 3365 universal testing machine, and the Izod impact test was performed using an Instron CEAST 9050 testing machine. The results indicated that the stitched specimens had comparable in-plane mechanical properties to the unstitched specimens. In the tensile mechanical test, the stitched specimens showed similar and 17.1% higher tensile strength compared to the unstitched specimens. The flexural mechanical test also demonstrated a 9% decrease in the flexural strength of the stitched specimens compared to the unstitched specimens. On the other hand, the Izod impact mechanical test showed a significant improvement by 33% in the stitched specimens compared to the unstitched specimens, which confirmed that stitching could successfully enhance out-of-plane mechanical properties. Overall, the findings of this research indicated that the stitched specimens had better mechanical performance compared to the unstitched specimens, and the reduction of the flexural strength was not significant as opposed to the considerable improvement of the impact strength.